Duy Nguyen: capstone - Nguyen, Duy, artist (Colorado State University. Libraries, 2015)
The artist's statement: In today's world, the need for clear, concise, visual communication is growing while technologies change and our means of communicating reach the world of digital and social media. The practice of graphic design has become more prevalent as a result of this need of conveying a clear message to the viewer. My work strives to be clear and concise through simplicity. Art, I believe, is the successful implementation of form and content that, done correctly, can effectively communicate a specific message. My work also explores different avenues of communicating the identity and core values of a particular brand. As a designer, I hope to bring this concept to others and provide a solution to their branding needs. My style and design sensibilities are always changing as technology and communication changes, so I must adapt to different projects and determine its purpose, core value, and the message it is ultimately trying to convey. I am influenced and inspired by designers such as Saul Bass, Paul Rand, Milton Glaser, and Paula Scher.
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.
Keywords: graphic design